A TODDLER SPEAKS OUT: PHYSIC AND MENTAL ATTAINMENT IN A SINGLE PARENTING - febti ismiatun; eko suhartoyo (Raheema, 2021)
Deriving from many cases in a single parenting that effects the children’s physic and mental development directs this study to be worth-conducting. This study aimed at investigating the toddler’s physical and mental growth in a single parenting through qualitative approach. A narrative design was employed to reveal the untold story of a toddler in a single parenting through participatory observation. Then narrative analysis was applied based on these procedures: (1) observing the research object, (2) classifying the data, (3) interpreting data, and (4) (re)checking the data interpretation with the subject of research in order to search out verification (Creswell & Poth, 2018). Afterwards, the results were found that a toddler could meet his basic needs of life from a single parent through three aspects, such as child’s physical-biological education, child’s spiritual education, and child’s socio-cultural education. Thus, this study has emphasized the potential of toodler’s physic and mental attainment in context. Suggestions were then presented at the end of this article.